1990
DOI: 10.1080/00071669008417318
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive senescence in domestic fowl: Effects on egg production, sequence length and inter‐sequence pause length

Abstract: 1. Age-related changes in egg production, oviposition sequence length and inter-sequence pause length were studied by analysis of oviposition records of 50 individually-caged broiler breeders from 24 to 62 weeks of age. 2. The 44 surviving hens exhibited a production profile characteristic of broiler breeders (184 eggs per hen), with a peak mean sequence length of 19 eggs at 32 weeks of age. Inter-sequence pause length was maximum (1.6 d) at 54 weeks of age. Overall, the hens averaged 48 sequences, with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 11 publications
5
33
1
1
Order By: Relevance
“…Total lag is a measure of the proportion of the day used for egg laying and can be regarded as an indication of the length of the open period for ovulation (Fraps, 1970). A shortening of the duration of the open period may reduce the ovulation rate and hence the rate of oviposition (Robinson et al, 1990). The differences in total lag found between genotypes are then in good agreement with and probably contributed to the observed differences in laying rates.…”
Section: Discussionsupporting
confidence: 69%
“…Total lag is a measure of the proportion of the day used for egg laying and can be regarded as an indication of the length of the open period for ovulation (Fraps, 1970). A shortening of the duration of the open period may reduce the ovulation rate and hence the rate of oviposition (Robinson et al, 1990). The differences in total lag found between genotypes are then in good agreement with and probably contributed to the observed differences in laying rates.…”
Section: Discussionsupporting
confidence: 69%
“…Under the parameters of this study, hens with a long prime sequence length were not prone to having reduced persistency of lay. Prime sequence length was correlated with both total egg production (r = 0.485) and to settable egg production (r = 0.478), concurring with previous research by Robinson et al (1990), which indicated a correlation r = 0.399 between prime sequence length and total egg production. The relationship between prime sequence length and egg production can be a useful criteria for the early selection of hens with high egg production potential.…”
Section: Sequence Lengthsupporting
confidence: 78%
“…Pauses in egg production were averaged into the average weekly sequence length as 0s. The prime sequence was defined as the longest egg sequence around the time of peak production (Robinson et al 1990). …”
Section: Laying Recordsmentioning
confidence: 99%
“…However, It is evident from these results that delalJd sexual maturity results in-longer prime sequences' and iherefore fewer sequences and fewer pause days' Prime ,.qu.n"" length is known to be correlated with total egg ""ipr, i" broller breeders (Robinson et al'.1990) …”
Section: Ggg)mentioning
confidence: 96%